Pengambilan Keputusan Mahasiswa dalam Memilih Perguruan Tinggi Swasta di Pekanbaru - Putri Wulandini S (JSSH (Jurnal Sains Sosial dan Humaniora), 2017)
Education has the very centraled and strategic role, esspecially, if it is accorded to the quality increasing effort of the human resources. Because only for the qualitified human resources will be created the truely human value and dignity increasing. University as one of the important part in the education zone which is responed in effort to enrich the nation life and the very strategic role to make the part in avoiding the the human resources quality problem. Amount of the many University if seen from the University perspective will cause the high competition in taking the pre-colligian. Answering the problem which is exposed above., the study aimed to determine the promotion activity contribution, price contribution, location contribution, facility and insfratucture contribution, human resources quality contribution through the colligian’s decision maker in choosing the private University. The used research design in the research was explanatory and confirmation research which amied to explain the causal relationship between variable through the hipothesis test and operated by the descriptive analysis maintain and verificative through the suvey. The research outcome was found the promotion contribution (p value 0.00), price contribution of p value =0,0001, location contribution p value = 0,0001, facility and infrastructure contribution p value = 0,0001, human resources quality contribution p value 0,0001 throught the decision maker on all relating statistically. Suggested for the private University management in Pekanbaru was more selective, critism to develop the University, for finding the students so that want to be able to study in the private University. (a) for the next research becomes the basic that when wanting the consument according to the target, besides promotion, location which must be noticed, completely facility, competitive price.